Rancang Bangun Sistem Pengendali Lampu Dan Kipas Angin Menggunakan Handy Talky - Ayu Anggi Wijaya; Elisah Silalahi (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
In this final project will be designed a controlling tool of lamp and fan, which can control remotely away with radio communication by using handy talky and DTMF (Dual Tone Multiple Frequency) system. This system consist of two parts named transmitter and the receiver, the transmitter uses keypad and encoder as a signal tone generator which will be sent via handy talky and at the part of receiver uses handy talky to receive the signal tone,the decoder will convert the frequency signal into four bits data, the buffer is used to lock the voltage logic, digital comparator as a comparison, flip-flop as bit counter that will provide input on the driver relay which connected to two loads i.e. lamp and fan. This tool is expected can control the lamp and fan away until five Km.